ROLA PAMIĘCI ROBOCZEJ W NAUCE JĘZYKA OBCEGO I WIELOJĘZYCZNOŚCI - Biedroń, Adriana (Neofilolog, 2018)
Working memory is now one of the most frequently studied individual differences in various fields of science, including cognitive and developmental psychology, neuroscience, and second language acquisition. It affects cognitive functioning, including all aspects of learning a foreign language, and its deficits severely impair learning outcomes. This article focuses on practical application of this knowledge (see Gregersen & MacIntyre, 2014) in a language classroom. To this end, we first present a definition of a working memory and its components altogether with their relevance for various areas of foreign language learning. This is followed by a review of research on linguistically gifted individuals, polyglots, and savants as well as bilinguals from the perspective of memory aptitude. The last section offers some pedagogical implications, such as aptitude-treatment interaction and working memory training. The article ends with suggestions for further research in this area.